Coxiella burnetiias a useful tool to investigate bacteria-friendly host cell compartments - Pechstein, Julian; Schulze-Luehrmann, Jan; Lührmann, Anja (International Journal of Medical Microbiology, 2017)
Coxiella burnetii is an obligate intracellular and airborne pathogen which can cause the zoonotic disease Q fever. After inhalation of contaminated aerosols alveolar macrophages are taking up C. burnetii into a phagosome. This phagosome matures to a very large vacuole called the C. burnetii-containing vacuole (CCV). Host endogenous and bacterial driven processes lead to the biogenesis of this unusual compartment, which resembles partially a phagolysosome. However, there are several important differences to the classical phagolysosome, which are crucial for the ability of C. burnetii to replicate intracellularly and depend on a functional type IV secretion system (T4SS). The T4SS delivers effector proteins into the host cell cytoplasm to redirect intracellular processes, leading to the establishment of a microenvironment allowing bacterial replication. This article summarizes the current knowledge of the microenvironment permissive for C. burnetii replication.
EVALuna2:7729